Efficacy and safety of edaravone for acute intracerebral haemorrhage: protocol for a systematic review and meta-analysis. Issue 8 (20th August 2020) - Feng, Luda; Liang, Ning; Li, Tingting; Yang, Qinyu; Jiang, Ping; Guo, Shengnan; Zhang, Chi; Gao, Ying
Abstract : Introduction: Intracerebral haemorrhage (ICH) is a life-threatening condition with no effective internal treatment options. However, edaravone is a promising therapeutic agent, although its beneficial effects are inconclusive based on previous systematic reviews and meta-analyses. While several trials in the last 8 years have reported the favourable long-term functional outcomes, a few reports indicated edaravone to be associated with an increase in adverse events. Methods and analysis: This protocol was performed in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. We will perform the comprehensive and manual search for published articles, ongoing trials, dissertations and grey literature. The following databases will be searched from inception to 23 April 2020: Medline, Embase, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Chinese scientific periodical database of VIP INFORMATION, Wanfang Data and SinoMed, with no language restrictions. All randomised controlled trials that (1) compared edaravone with placebo or no treatment, and (2) compared edaravone plus routine treatment or cointervention with routine treatment or cointervention for treating acute ICH will be included. Mortality and long-term dependency will be the primary outcomes. The incidence of adverse events will be assessed for safety evaluation. Two reviewers in pairs will independently carry out the article selection, data extraction and quality assessment. Assessment of the risk of bias and data synthesis will be performed using software Review Manager V.5.3. Finally, we will use the Grading of Recommendations Assessment, Development and Evaluation approach to evaluate the quality of the overall evidence. Ethics and dissemination: There are no ethical considerations associated with this updated systematic review and meta-analysis. The findings will be disseminated in peer-reviewed journals or conference presentations. PROSPERO registration number: CRD42019147801.